PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP BANGUN RUANG DAN KETERAMPILAN SOSIAL SISWA KELAS V SD - Aisyah Ramadhani Putri; Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students' understanding of three-dimensional shapes and their social skills through the implementation of collaborative learning. This research was based on initial observations of fifth-grade students at SDN Pendem 01 Kota Batu, which revealed that social skills such as cooperation and communication within groups, as well as understanding of three-dimensional shapes, were still relatively low. This research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The research subjects were 30 fifth-grade students. During the intervention, students were divided into heterogeneous groups and assigned to create three-dimensional shape models using rolled paper. Data were collected through observation, interviews, documentation, and concept comprehension tests, and were analyzed using descriptive qualitative and quantitative methods. The results showed that collaborative learning significantly improved students’ conceptual understanding, as evidenced by the increase in average scores from 61.2 in the pre-test to 83.4 in the post-test, with an N-gain score of 0.585, categorized as moderate. Moreover, students' social skills, including teamwork, communication, and responsibility, also improved throughout the learning process. This study confirms the effectiveness of collaborative learning in enhancing both cognitive and social aspects of students’ development, in line with Vygotsky’s and Slavin’s theories emphasizing the role of social interaction in learning.